A comparison of social prescribing approaches across twelve high-income countries - Scarpetti, Giada (2024)
Funding Information: Different funding mechanisms have been exploited for social prescribing programs such as philanthropic funding, government funding, health insurance reimbursements, and research funds. In Australia, funding comes from a mixture of philanthropic and charitable organisations, as well as some state government funding. Similarly, in Canada funding sources differ based on the project with some funding from the provincial Ministry of Health and other funding from private donors/foundations. In Austria, social prescribing is funded by funding calls from the Ministry of Social Affairs, Health, Care and Consumer Protection. Similarly, in the US, most of the funding has been obtained through grants or research funds for randomized control trials, testing the effectiveness of social prescribing. Generally, health insurance companies do not provide these services in the US, although state Medicaid Managed Care Organizations have started to pay for link workers. Funding Information: Some countries pay for link workers through a salaried position. Starting in 2019, NHS England has paid 100% reimbursement of the salary of a full-time social prescribing link worker for every 13,000 patients. With this, link workers became salaried employees of primary care practices. In Germany, health insurances are the primary funder for link workers’ salaries (e.g., for Hamburg/Billstedt four large health insurance funds are partners). In Slovenia, health-related NGOs are funded by the Ministry of Health and/or municipalities, while primary health care services, including health promotion centers, are funded by the National Health Insurance Fund. Workers in the social sector are funded through the Ministry of Labour, Family, Social Affairs and Equal Opportunities. In Wales, most link workers are employed on fixed-term contracts paid for by the integrated care fund, GP cluster funding, health boards or local authorities [27] . The pilot project in Lapland, Finland, is funded by the Ministry of Social Affairs and Health. In Portugal, link workers’ salaries are funded through the budget allocated to the FHU and supported by the municipality, requiring no additional remuneration. Similarly, in the Netherlands, link workers are funded exclusively by municipalities. Publisher Copyright: © 2024